Bursts of non-deglutitive simultaneous contractions may be a normal oesophageal motility pattern. Issue 8 (August 1993) - Janssens, J; Annese, V; Vantrappen, G
Abstract : The frequency and characteristics of non-deglutitive motor activity of the human oesophagus and its relation to motility patterns in the antrum and upper small intestine were studied in 25 fasted healthy subjects. Motility of the oesophagus, antrum, and upper small intestine was recorded by means of a manometric perfused catheter system. The most striking non-deglutitive motility pattern consisted of repetitive bursts of non-sequential pressure peaks occurring in the smooth muscle portion of the oesophagus. The mean number of pressure peaks per burst was 2.7 (SD 2) waves with a mean amplitude of 19.5 (SD 9.9) mm Hg and a duration of 3.09 (SD 0.22) seconds. The highest amplitude was 80 mm Hg and the longest burst consisted of 13 repetitive waves. The bursts were recorded up to a distance of 15-20 cm above the lower oesophageal sphincter. Ninety five per cent of the bursts occurred during a 15 minute period before the onset of phase 3 of the migrating motor complex in the antral or upper small intestinal area, or during the lower oesophageal sphincter component of the migrating motor complex. In conclusion, spontaneous bursts of non-sequential pressure peaks occurred in the smooth muscle part of the human oesophagus in relation to phase 3 of the migrating motor complex. They represent the oesophageal body component of phase 3 of the migrating motor complex and are not a sign of oesophageal motor abnormalities.